PENGARUH VISUALISASI TARI BEDANA TERHADAP PENGUATAN NILAI-NILAI KEARIFAN LOKAL DAN EDUKASI BUDAYA DI PROVINSI LAMPUNG - Saputra, M Naruli; Janah, Laelatul; Ziddan, Amri Sukroeni; Sumargono, Sumargono (Institut Seni Indonesia Surakarta, 2024)
Traditional arts, or regional arts, are inherited and passed down from generation to generation in the archipelago, and will experience development from generation to generation. In reality, it is not easy for traditional arts to maintain their existence and are faced with the current of globalization which is currently getting bigger. Bedana dance as a type of traditional Lampung dance is a symbolic embodiment of customs and religion and has become integrated with Lampung society. Bedana dance has lived and developed in the Lampung area along with the arrival of Islam, so it is not surprising that in other regions in Indonesia it has similarities in both variety and movement, which also has the same function, namely Social Dance which has an Islamic spirit. This research aims to see the effect of providing visualization treatment on strengthening local wisdom values ​​and cultural education in the Lampung Province region. This research uses an experimental method with a one group pretest-posttest design. The results of research carried out in the Lampung region show that after being given treatment to the community using Bedana dance visualization, there is a difference in pretest and posttest scores on the value of local wisdom and cultural education in Lampung province with a sig (2-tailed) value of 0.000, which is smaller. compared to the α value, which is 0.05, therefore Ho is rejected, meaning there is an average difference between the pretest score and the posttest score.